The Literacy Development: Unveiling the Role of Balai Poestaka: A Historical Study - Nurmalina; SA., Romli; Rochmiatun, Endang (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
The existence of Balai Poestaka was aimed to facilitate the Dutch East Indies Government in monitoring the circulation of